Reflections on IDEAL: What we have learnt from a unique calf cohort study - Callaby, R.; Jennings, A.; Mwangi, S.T.; Mbole-Kariuki, M.; Wyk, Ilana Conradie van; Kiara, Henry K.; Coetzer, Jacobus A.W.; Woolhouse, Mark E.J.; Hanotte, Olivier H.; Toye, Philip G.; Bronsvoort, B.M. de C. (Elsevier, 2020)
The year 2020 marks a decade since the final visit was made in the 'Infectious Diseases of East African Livestock' (IDEAL) project. However, data generation from samples obtained during this ambitious longitudinal study still continues. As the project launches its extensive open-access database and biobank to the scientific community, we reflect on the challenges overcome, the knowledge gained, and the advantages of such a project. We discuss the legacy of the IDEAL project and how it continues to generate evidence since being adopted by the Centre for Tropical Livestock Genetics and Health (CTLGH). We also examine the impact of the IDEAL project, from the authors perspective, for each of the stakeholders (the animal, the farmer, the consumer, the policy maker, the funding body, and the researcher and their institution) involved in the project and provide recommendations for future researchers who are interested in running longitudinal field studies.